2015
DOI: 10.3389/fnhum.2015.00605
|View full text |Cite
|
Sign up to set email alerts
|

Neural Patterns of the Implicit Association Test

Abstract: The Implicit Association Test (IAT) is a reaction time based categorization task that measures the differential associative strength between bipolar targets and evaluative attribute concepts as an approach to indexing implicit beliefs or biases. An open question exists as to what exactly the IAT measures, and here EEG (Electroencephalography) has been used to investigate the time course of ERPs (Event-related Potential) indices and implicated brain regions in the IAT. IAT-EEG research identifies a number of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 59 publications
2
33
2
Order By: Relevance
“…Results indicating a two-factor structure further support the ideation-to-action framework of suicidality which highlights the existence of both long-standing suicide risk factors and acute warning signs for imminent suicide (Klonsky & May, 2014;Rudd et al, 2006). Findings from the current study identify Stress, Agitation, and Psychological Pain as possible warning signs for adolescent suicide risk, whereas Self-Hate and Hopelessness are potential long-term risk factors.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Results indicating a two-factor structure further support the ideation-to-action framework of suicidality which highlights the existence of both long-standing suicide risk factors and acute warning signs for imminent suicide (Klonsky & May, 2014;Rudd et al, 2006). Findings from the current study identify Stress, Agitation, and Psychological Pain as possible warning signs for adolescent suicide risk, whereas Self-Hate and Hopelessness are potential long-term risk factors.…”
Section: Discussionsupporting
confidence: 68%
“…Although the UPPS-P was designed to assess traits, and the Agitation item on the SSF-4 assesses a more statespecific level of Agitation, similar measures have been used in past SSF validation studies as a proxy measure of Agitation (Conrad et al, 2009). Both high negative urgency and Agitation have been found to associate with suicide behavior (Busch, Fawcett, & Jacobs, 2003;Klonsky & May, 2010). This subscale is made up of 12 items (ex.…”
Section: Suicide Status Form For Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, one could consider using multimodal measures to further investigate cognitive processes involved in completing implicit measures. For example, Healy et al (2015) demonstrated that Electroencephalography could be used to examine the extent to responses to implicit measures are resulting from automatic association (activation) or context factors, by relating neural activity to different phases in the IAT. Both the advanced modeling and multimodal approaches could contribute to our understanding of implicit attitudes within the educational area.…”
Section: Resultsmentioning
confidence: 99%
“…Recordings were taken from 32 scalp electrodes based on the 10/20 system, with a ground electrode at Fpz. Electrodes were referenced online to a virtual ground point (i.e., reference-free acquisition) formed within the amplifier (Luck, 2014), a method used in previous studies (Healy, Boran, & Smeaton, 2015; Novak & Foti, 2015; Weiler, Hassall, Krigolson, & Heath, 2015). The electrooculogram was recorded from two auxiliary electrodes places 1 cm above and below the left eye, forming a bipolar channel.…”
Section: Methodsmentioning
confidence: 99%